Guidelines and Current Assessment of Health Care Responsibility in Italy - Zerbo S; Malta G; Argo A (Dove Medical Press, 2020)
Stefania Zerbo, Ginevra Malta, Antonina Argo Department of Health Promotion, Maternal and Child Care, “G. D’Alessandro”, Legal Medicine Section, University of Palermo, Palermo, ItalyCorrespondence: Stefania ZerboDepartment of Health Promotion, Maternal and Child Care, “G. D’Alessandro”, Legal Medicine Section, University of Palermo, via del Vespro N. 129, Palermo 90127, ItalyTel +39 33 3725 0209Fax +39 09 1655 3203Email stefania.zerbo@unipa.itAbstract: Clinical guidelines are a potential tool for improving the effectiveness and quality of healthcare, decreasing variability in clinical practice, and preventing adverse events. In the purview of Law no. 24/2017, adherence to national guidelines can lead to a reduction in medical malpractice claims and the practice of so-called “defensive medicine”. The law has assigned a central role to the guidelines, establishing the National Institute of Health through the new Italian National Center for Clinical Excellence, Quality, and Security (CNEC) as the methodological guarantor in the process of national guideline development. Here we discuss the issue of professional liability as recently outlined by the Gelli-Bianco Law (no. 24/2017), taking into account the clinical significance and medicolegal value of the guidelines.Keywords: clinical guidelines, health care, liability, medical malpractice, Gelli-Bianco law